Viewing the capitalist world-system through (inter-)city lenses: rationale, methodology and first results - Ben Derudder (Belgeo)
This paper explores how a geographically detailed assessment of the world-city network may serve as an alternative mapping of the capitalist world-system. The first section of this paper looks at the theoretical rationale for this city-based approach. The second section presents a re-interpretation of the existing body of literature on transnational urban networks in a world-systems framework, i.e. some of the existing world city-narratives will be re-envisaged as «world-cities in a world-system». Based on this world-systems re-interpretation, the third section provides a formal specification of the world-city network as an inter-locking network where relations between world-cities are defined through the aggregation of relations between sub-nodal capitalist agents. The fourth section elaborates on the general patterns that arise from an exploratory analysis of 234 cities in the capitalist world-system, and hints at how these patterns may serve as an alternative mapping of the tripolar division of the capitalist world-economy.